What Drives the Diversification of Eyespots in Morpho Butterflies? Disentangling Developmental and Selective Constraints From Neutral Evolution - Debat, Vincent; Chazot, Nicolas; Jarosson, Silvère; Blandin, Patrick; Llaurens, Violaine (Frontiers in Ecology and Evolution, 2020)
Eyespots are wing colour pattern elements repeatedly observed in many butterflies, whose developmental genetics has been extensively documented. Nevertheless, the evolutionary forces shaping their diversification across species still remain largely unknown. Here we investigate the evolution of eyespots in the 30 species of the neotropical genus Morpho. Morpho butterflies display a series of eyespots located on the ventral side of their wings, highly variable among species, ranging from large, conspicuous structures to relictual spots. Applying geometric morphometrics to a large sample (N = 910) spanning all Morpho species and both sexes, we assess eyespots number, position, size and shape. We detect a divergence in eyespots position between understory and canopy species that opposes an L-shaped configuration in canopy species to a line pattern in understory species, where the eyespots tend to fuse and form a stripe in white and pale species. This effect is stronger than expected based on a Brownian motion model of phylogenetic divergence, suggesting an adaptation to the microhabitat and an influence of the wing colour on the evolution of pattern elements. Remarkably, this shift in colour pattern is strongly correlated with a shift in wing shape. However, using a thin-plate spline interpolation, we show that the shape change is insufficient to explain the evolution of eyespots position as a developmental side-effect of wing shape evolution, also pointing at an adaptive effect. Finally, we find a significant negative correlation between eyespot relative size and the within-species variation in eyespot number, position, size and shape, suggesting a relaxed or apostatic selection on small eyespots. We hypothesize that contrasted ecology may explain the observed differences between species: large and phenotypically stable eyespots might act as attack deflectors; small, variable faded eyespots might rather enhance crypsis; and pale species stripe pattern might disrupt the outline of the wing.